Pengaruh Customer Relationship Management & Brand Image terhadap Kepuasan Pasien Rawat Jalan selama Masa Pandemi Covid-19 - Annisah Syairah Ferianda; Danang Indrajaya; Abdul Haris Muchtar (Peneliti.net, 2022)
The condition of health services in Jambi province still needs to be addressed. Many reports from the public, stated that most of the hospitals did not have good service quality. This study focuses on customers, especially outpatients at Baiturrahim Hospital to examine the effect of Customer Relationship Management & Brand Image on Outpatient Satisfaction during the Covid-19 Pandemic (Study at Baiturrahim Hospital Jambi). The research method used is a quantitative type with a descriptive nature by distributing questionnaires to 233 outpatients at the Baiturrahim Hospital during the Covid-19 pandemic in 2020. The distribution of questionnaires uses a Likert scale and is processed using SmartPLS 2.0 software. This research has met the evaluation test of the measurement model and the evaluation of the structural model with valid and reliable results. The biggest influence is the influence of the Customer Relationship Management (CRM) variable on the Customer Satisfaction variable. Then followed by the influence of the Brand Image variable on the Patient Satisfaction variable. The conclusions of this study are (1) there is a significant positive effect of the Customer Relationship Management (CRM) variable on the Patient Satisfaction variable and (2) there is a significant positive effect of the Brand Image variable on the Patient Satisfaction variable